PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI KERJA TERHADAP KOMITMEN KERJA KARYAWAN PERGURUAN TINGGI SWASTA - Riyadini Riyan Utami (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2017)
Employee contributions to the organization are very dominant, because employees are producing work for the organization, ie, each job in the organization is always carried out by employees. Success or failure of an organization depends largely on the human element that doing so is necessary to fringe benefits to employees in accordance with the nature and circumstances. Some of the problems seen in the private university,include uneven incentives for each employee. The provisions on incentives is still no clarity, this can happen because there are no binding regulations on the definition or provision of incentives. Another problem is the lack of employee commitment to the company. Research to be conducted research kind of explanation (explanation) or explanatory research that uses the same data, explain causal relationships between variables through hypothesis testing, with respondents as many as 64 people. Keywords: Incentives, Motivation, performance